Elektrofiziološka ocena mrežnice otrok s prirojenim nistagmusom - Kurent, Alma (Zdravniški vestnik, 2012)
Background: Electroretinography (ERG) enables assessment of the retinal function and facilitates the diagnostics of congenital nystagmus in children. The aim was to review the three categories of congenital nystagmus according to the clinical picture in relation to ERG findings: sensory, neurological andidiopathic nystagmus. Methods: This was a 5-year retrospective study (from January 2006 to December 2010). The study included 100 children with congenital nystagmus (mean age 2.3 years). ERGs were recorded with skin electrodes in alert children without pupil dilatation, as response to white scotopic flash, blue flash, red flash, white photopic flash and 30 Hz flicker stimuli. Results: Abnormal ERG in both eyes was found in 20 of the 100 children under the study. Sensory nystagmus was classified in 40 of the children, in 12/40 of the children with abnormal ERG the following retinal abnormalities were observed: Leber congenital amaurosis in 6/12 children, suspected congenital stationary night blindness in 3/12 children and suspectedachromatopsia in 3/12 children. In the group of neurological nystagmus (35 children) 5 children had abnormal ERG that could not be explained in the context of broader clinical picture. In the group with idiopathic nystagmus (21 children) all chidren had normal ERG.Conclusions: In infants with congenital nystagmus, it is possible to record ERGs with skin electrodes that can provide important information on normal or abnormal retinal function already in the first few months after birth.
Keywords: akromatopsija; elektroretinografija; Leberjeva kongenitalna amavroza; prirojena stacionarna nočna slepota; prirojeni nistagmus; vidna elektrofiziologija